CARDIOPROTECTIVE ACTIVITY OF CALLIANDRA PORTORICENSIS LEAF ETHANOL EXTRACT AGAINST KEROSENE VAPOUR INDUCED CARDIOTOXICITY IN MALE ALBINO RATS - Ese, Siemuri Ogugu; Oyewale, Adetunji Abisoye; Omolara, Kamson Risqat; Nyiam, Edward Bridget (Universal Journal of Pharmaceutical Research, 2023)
Aim and objective: This study investigated the cardioprotective activities of Calliandra portoricensis leaf ethanol extract (CPLEE) on kerosene vapour–induced cardiotoxic male albino rats. Methods: Twenty-five male albino rats (120-150 g) were grouped into five groups (n=5). Group 1 received distilled water (normal control), while CPLEE constituted doses of 25 and 50 mg/kg b.wt p.o were administered once daily for the last 4 weeks to animals in group 4 and 5 respectively. Group 2 received kerosene vapour1.0 mL/kg body wt by inhalation for 4 weeks to induce toxicity, while group 3 received vitamin C 200 mg/kg p.o. Serum and cardiac samples were collected and used for the biochemical analyses. Results: Qualitative phytochemical analysis of CPLEE revealed the presence of different phytochemicals including flavonoids, tannin, saponin, alkaloids, cardiac-glycosides, etc. CPLEE caused a significant reduction (p<0.05) in the serum levels of ALT, AST, ALP and LDH in the treated kerosene vapour groups in contrast to the untreated kerosene vapour induced cardiotoxic group. CPLEE showed potentials to mop-up free radicals generated by kerosene, by significantly reducing (p<0.05) lipid peroxidative-product (malondialdehyde, MDA) levels and increasing antioxidant activities of superoxide dismutase, catalase and reduced glutathione (GSH) in dose dependent manner in the treated kerosene vapour groups compared to the untreated kerosene vapor-induced cardiotoxic group. Conclusion: The findings suggests that the CPLEE have the capacity to improving cardiac functions at safe doses possibly due to its abundant phytochemicals and antioxidants that offers protections against kerosene vapour-induced oxidative-damage. Peer Review History: Received: 9 June 2023; Revised: 10 July; Accepted: 28 August; Available online: 15 September 2023 Academic Editor: Dr. Iman Muhammad Higazy , National Research Center, Egypt, imane.higazy@hotmail.com Reviewers: Dr. Sangeetha Arullappan, Universiti Tunku Abdul Rahman, Malaysia, sangeetha@utar.edu.my Prof. Ali Gamal Ahmed Al-kaf, Sana'a university, Yemen, alialkaf21@gmail.com